Analisis Manajemen Risiko Operasional pada Produk Tabungan Haji di BPRS Bhakti Sumekar Cabang Madya Pamekasan - Rahman, Musyfiqur; Umam, Khotibul (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
Hajj savings is an important product in Islamic banking that assists Muslims in financially planning their pilgrimage. This study analyzes the implementation of operational risk management on the hajj savings product at BPRS Bhakti Sumekar Cabang Madya Pamekasan, aiming to identify the supporting factors, obstacles, and its impact on product success. A qualitative method was employed through observation, interviews, and documentation to comprehensively collect primary and secondary data. The analysis shows that effective risk management practices, such as the use of the digital Setrik application and standardized procedures, can minimize operational risks like human errors and fraud. The main supporting factors include quality human resources, adequate technology, and customer loyalty; while the obstacles consist of limited network coverage in remote areas, account officers’ time management, and low technological literacy among elderly customers. The positive impacts of effective risk management include increased customer satisfaction and growth in the hajj savings portfolio, whereas neglecting operational risk may cause financial losses and erosion of customer trust. The study’s implications emphasize strengthening the integration between risk management and business strategies to ensure the sustainability and competitiveness of Islamic banking.